The determinants of university dropout: A review of the socio-economic literature. (February 2022) - Aina, Carmen; Baici, Eliana; Casalone, Giorgia; Pastore, Francesco
Abstract: This article provides a comprehensive review of the socio-economic literature on the student determinants of tertiary education dropout, in order to help research scholars better understand this phenomenon. Empirical findings are framed within a theoretical model that analyzes higher education choices and prospective outcomes in a dynamic setting, where informative issues (emphasized by the economic literature) and relational ones (emphasized by the sociological literature) are crucial to predicting students' achievements. Our review suggests that student university persistence/attrition depends on a mix of individual, institutional, and economic factors, the effects of which on the dropout decision are mediated by a student's ability to integrate into the academic system. Some factors are given, and their effects are valuable only in a descriptive perspective. Others, instead, can be manipulated by the decisionmakers in the tertiary education system and, as such, are more interesting from the policymaker's viewpoint. In particular, all interventions aimed at fulfilling the initial informational gap of students and at improving their integration into academic and social life are key to study success. Highlights: Student attrition is an ongoing challenge for universities. The socio-economic literature of dropout is analyzed within a unified framework that combines the human capital model with models that emphasize the relational features of the university experience. Acquiring new information, students revise their opportunity costs and may drop out. Early university withdrawal, ceteris paribus, is lower for academically and socially integrated students. Informational and relational issues are crucial in explaining the dropout phenomenon.